Threatening Utterances In The English Translation Of Bukhari Prophetic Tradition: A Pragmatic Perspective - Sari, Annisa Puspita, Siti Zurhriah Ariatmi, M. Hum, Drs. Maryadi M. A. (2014)
This research is aimed to describe the pragmalinguistics forms and to describe type of the implicature of the threatening utterances taken from the English Translation of Bukhari Prophetic Tradition. The data taken from 50 chapters of Bukhari Prophetic tradition downloaded from www.hadithcollection.com which is posted in 2008. This research is using descriptive qualitative research and using documentation method to collect the data. The data is 25 threatening utterances taken from English Translation of Bukhari Prophetic Tradition. Threatening Utterances in English Translation of Bukhari Prophetic Tradition: Pragmatic Perspective is using the theory from Grice for analyzing the implicature and the theory from Anna Torsborg to analyze the pragmalinguitics. This research finds conventional implicature took 60% and particularized took 40%. While Lexical intensification took 60% and commitment upgraders took 40 %. In this research the generalized conversational implicature cannot be found. Also the downgraders as internal modification has not found in this research. The pragmalinguistic found lexical intensification is mostly used in the threatening utterances reflected that swearing in thretening utterances is effective way to express the threatening and to make the followers be careful in face the life. While the conventional impplicature is the most type of implicature used in the threatening utterances in Bukhari prophetic tradition reflected the threatening utterances shared delivering the messages inside the thretening utterances and it is delivered directly by using the conjunction 'but' and 'and'. The researcher by this research proposed some suggestion by the thretening whether the Muslim, Non Muslim, Engish teacher, Students and the fut ure researcher will take more intention in pragmatic study to analyze the threatening utterances using pragmatic perspective or the branches of the pragmatic like implicature and pragmalinguistics. Then, the threatening utterances is not the negative way w hich is done by the Prophet because inside the thretening the kindness of the Prophet appeared.